2000
DOI: 10.2139/ssrn.223635
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Suggestion: Inertia in 401(k) Participation and Savings Behavior

Abstract: Research support from the National Institute on Aging is gratefully acknowledged. A special thanks to Hewitt Associates for their help in providing the data. Thanks also to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

75
1,256
4
10

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 952 publications
(1,345 citation statements)
references
References 34 publications
75
1,256
4
10
Order By: Relevance
“…Housing and retirement decisions are the biggest financial decisions people make in their lifetimes, and prior research has shown that house buying (Simonsohn & Loewenstein, 2006) and selling (Genesove & Mayer, 2001) are influenced by contract effects and loss aversion respectively, and that participation in retirement savings program (Madrian & Shea, 2001) and the amount of money saved (Thaler & Benartzi, 2004) are influenced by defaults and simple commitment devices respectively. Why may implicit egotism not matter for marriage, occupational and location decisions then?…”
Section: When Do Psychological Taste Shifters Influence Real Decisions?mentioning
confidence: 99%
“…Housing and retirement decisions are the biggest financial decisions people make in their lifetimes, and prior research has shown that house buying (Simonsohn & Loewenstein, 2006) and selling (Genesove & Mayer, 2001) are influenced by contract effects and loss aversion respectively, and that participation in retirement savings program (Madrian & Shea, 2001) and the amount of money saved (Thaler & Benartzi, 2004) are influenced by defaults and simple commitment devices respectively. Why may implicit egotism not matter for marriage, occupational and location decisions then?…”
Section: When Do Psychological Taste Shifters Influence Real Decisions?mentioning
confidence: 99%
“…It may take years before labor and housing markets fully adjust to tax changes. Similarly, the behavioral literature suggests that people might delay altering their savings behavior (Madrian and Shea 2001). Furthermore, while income can be shifted between sources (e.g., between Subchapter C and Subchapter S, as mentioned earlier), these decisions may be costly to reverse, and some may delay making changes until they better understand the costs and benefits of such changes.…”
Section: Short-and Longer-run Responsesmentioning
confidence: 97%
“…13. Perhaps the most striking example is the study of Madrian and Shea (2001), showing that a change in the default option for enrollment in an employer-provided pension plan had an enormous impact on enrollment and pension contribution decisions.…”
Section: Notesmentioning
confidence: 99%